Sustainable energy technologies - Chattopadhyay,G.P (Atlantic, 2015)
Every individual, organisation, or society uses energy in some form or the other. Increase in world population, and consequent material consumption in both the developing and the developed hemispheres is leading to a phenomenal increase in world energy requirements. The challenge is not only to satisfy this huge energy need but also to look out for ways to secure affordable and sustainable energy.